Agency costs, ownership structure and corporate governance mechanisms - Singh, Manohar; Davidson III, Wallace N (Journal of Banking & Finance, 2003)
In this paper, we extend the work of Ang et al. [J. Finance 55 (1999) 81] to large firms. We find that managerial ownership is positively related to asset utilization but does not serve as a significant deterrent to excessive discretionary expenses. Outside block ownership may only have a limited effect on reducing agency costs. Furthermore, smaller boards serve the same role, but independent outsiders on a board do not appear to protect the firm from agency costs. Thus, this paper reports complementary evidence to Ang, Cole and Lin. In large publicly traded corporations, managerial ownership significantly alleviates principal–agent conflicts even in the presence of other agency deterrent mechanisms.